Reconstruction of the Legislative Authority of the Regional Representative Council in the Context of Optimizing the Position of the Regional Repre-sentative Council as a Representative Institution - Arifin, Firdaus (IHSA Institute, 2024)
Indonesia as a democracy so that the government is carried out from the people to the people through elected representatives, the influence of the concept of democracy and the sovereignty of the people forms a government based on the will of the majority to carry out the interests of everyone. There is a state institution called the Regional Representative Council as one of the legislative institutions, but the legislative authority owned by the Regional Representative Council tends to be weak compared to the House of Representatives. This research is a normative juridical research, with statute approach and conceptual approach, secondary data is obtained through literature review and then analyzed qualitatively juridically. The results of the study state that juridically the Regional Representative Council has a position as a high state institution that is mandated directly in the constitution, so that the Regional Representative Council is included in the costitutional state organ, but the legislative authority possessed by the Regional Representative Council according to the constitution is quite weak and tends to be a complement to the House of People's Representatives. Thus, it is necessary to strengthen the limited legislative function of the Regional Representative Council, this is in line with the fourth precept of Pancasila. It is also worth considering the use of a strong bicameral system